2020
DOI: 10.1002/ps.5784
|View full text |Cite
|
Sign up to set email alerts
|

Multiple point mutations in PsORP1 gene conferring different resistance levels to oxathiapiprolin confirmed using CRISPR–Cas9 in Phytophthora sojae

Abstract: BACKGROUND: Oxathiapiprolin is among the first commercial oxysterol-binding protein inhibitors (OSBPIs) developed by DuPont Corporation and shows excellent activity against plant-pathogenic oomycetes. Although more than 21 target site mutations have been identified in insensitive oomycetes, only G770V, G839W, and ΔN837 have been verified to confer oxathiapiprolin resistance in Phytophthora capsici or P. sojae. The effect of other mutations on OSBPIs sensitivity requires urgent investigation. RESULTS: P. sojae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 29 publications
1
55
0
Order By: Relevance
“…However, our results are unusual in that only a single copy of the transgene is inserted into the genome, at the Avr1b-1 locus. Our results are also unusual because other studies have reported normal expression of incoming transgenes after gene replacements at other Phytophthora loci (Ma et al, 2017;Miao et al, 2020;Ochola et al, 2020).…”
Section: Discussionsupporting
confidence: 47%
“…However, our results are unusual in that only a single copy of the transgene is inserted into the genome, at the Avr1b-1 locus. Our results are also unusual because other studies have reported normal expression of incoming transgenes after gene replacements at other Phytophthora loci (Ma et al, 2017;Miao et al, 2020;Ochola et al, 2020).…”
Section: Discussionsupporting
confidence: 47%
“…10 Phytophthora sojae transformants containing 16 mutations in the OSBP gene were recovered using the CRISPR-Cas9 system half of which associated with high resistance factors. 22 A deletion at position N837 was also reported to confer resistance to oxathiapiprolin in Phytophthora capsici and Phytophthora sojae. More recently, seven heterozygous point mutations in the target protein were found in Phytophthora capsici mutants resistant to fluoxapiprolin, another OSBP inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, P. sojae transformants containing amino acid changes of L733W, S768F/Y/K/I, G770V/L/P/A, N837Y/F/I, I877Y/F, G839W, P861H, L863W, and ΔG818/F819/837 in the target protein also showed oxathiapiprolin resistance to various extents. , A similarity of structure and host range, as well as strong cross-resistance, have been found between R034-1 and oxathiapiprolin. In addition, oxathiapiprolin-resistant mutants HNJZ10-E and LP3-M were also less sensitive to the compound R034-1, and R034-1-resistant mutants also had stably inherited resistance to oxathiapiprolin.…”
Section: Discussionmentioning
confidence: 91%
“…We speculate that different amino acid substitutions or a deletion at the same position could cause different changes in the protein structure, thereby affecting the binding of fungicide to the target protein. Miao et al also found that P. sojae transformants containing S768F/Y, G770V, N837Y/F, and I877Y in PsORP1 conferred high oxathiapiprolin resistance, but transformants containing S768I, G770L/P/A, N837I, and I877F exhibited low oxathiapiprolin resistance.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation